Effectiveness of Risk Management of Credit Risks of Life Insurance Companies in the Private Sector in India - Hariharan, B. R.; Sailaja, Vedala Naga (Indian Journal of Finance, 2017)
This article attempted to study the effectiveness of credit risk management of life insurance companies in the private sector in India and also the role played by the Indian insurance regulator (IRDAI) during the period under study by the public disclosures available. This was done by studying the following public disclosures of life insurance companies : (a) details regarding debt securities (investment assets rating profile), (b) details of non-performing assets, (c) statement of downgraded investments, and (d) loans given against life insurance policies.